Rethinking International Flows of Aid to Higher Education - Rensimer, Lee; McCowan, Tristan (International Higher Education, 2024)
Higher education has resurfaced as a key pillar for delivering the Sustainable Development Goals (SDGs) and tackling global challenges; however, international support to higher education systems and students in low- and lower middle-income countries remains misunderstood and poorly documented. With a marked increase in unreported funding from emerging donors, self-serving “aid,” and SDG-linked research funding vehicles, we argue it is time to rethink what counts as international aid to higher education.